2017
DOI: 10.1002/iid3.201
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in rate, triggers, and management in pediatric and adult cases of suspected drug‐induced anaphylaxis in Canada

Abstract: IntroductionData is sparse on drug‐induced anaphylaxis (DIA) and there have not been studies assessing the differences in clinical characteristics and management of DIA between adults and children.ObjectiveWe assessed the percentage, diagnosis, and management of DIA among all anaphylaxis visits in three pediatric and one adult emergency departments (ED) across Canada.MethodsChildren presenting to the Montreal Children's Hospital (MCH), British Columbia Children's Hospital (BCCH), and Children's Hospital at Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
2
18
2
2
Order By: Relevance
“…NSAIDs anaphylaxis is at the second rank as triggers of pediatric drug‐induced anaphylaxis. Of note, NSAID hypersensitivity ranks at the first place in few epidemiologic studies …”
Section: Culprit Drugsmentioning
confidence: 99%
“…NSAIDs anaphylaxis is at the second rank as triggers of pediatric drug‐induced anaphylaxis. Of note, NSAID hypersensitivity ranks at the first place in few epidemiologic studies …”
Section: Culprit Drugsmentioning
confidence: 99%
“…Regarding SCARs, the drugs involved depend on the population (adults or children). In this sense, antibiotics and anticonvulsants are the most common ones in adults ; and antibiotics, NSAIDs, and chemotherapeutics as well as aromatic anticonvulsants and also allopurinol are the most frequently involved in children . Over the last years, DHRs to new drugs as monoclonal antibodies, sulphasalazine and antituberculosis drugs have also been reported .…”
Section: The Burden Of Drug Hypersensitivitymentioning
confidence: 99%
“…This indicates the need to accurately evaluate these patients to reduce unnecessary inpatient/outpatient use of second‐line treatments that may otherwise produce greater use of hospital resources . In children with suspicion of DHRs to different drugs, from which NSAIDs and BLs were the most frequent, less than 10%‐20% of cases were confirmed as allergic . This mislabelling could be due to the fact that some symptoms (gastrointestinal or headache) are falsely considered as allergic, the virus and antibiotic interaction or the underlying infection itself can lead to cutaneous reactions, the low sensitivity of skin testing (STs) and the natural history with spontaneous resolution over time .…”
Section: Mislabelling Influences Dhr Real Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Parenteral administration, particularly via the intravenous route, has already been defined as a risk factor for drug-induced anaphylaxis [11, 42]. Another study analyzing cephalosporin-related adverse reactions retrospectively found that physician-documented anaphylaxis ratios due to oral or parenteral administration of cephalosporins were similar; our study once more points out the importance of the route of drug administration for the development of anaphylaxis, independent of the type of causative drug [43].…”
Section: Discussionmentioning
confidence: 74%